Konsekuensi Hukum Cacat Kehendak dalam Pembentukan Perjanjian Berdasarkan Pasal 1320 Kitab Undang-Undang Hukum Perdata - Ahmad Jalaludin Arrodli; Andika Ramadhan; Anggita; Denis Zakia Muhammad; Depi Dwi Pamungkas (Letterlijk, 2024)
Basically, in forming an agreement or contract must be based on the legal provisions governing the matter. The treaty is governed by article 1313 of the Covenant, whereas the legal conditions governing the treaty are regulated in article 1320 of that treaty. Nevertheless, any agreement that does not meet those conditions. One of them is a defect of the will that occurs in violation of article 1320 of the Covenant, and has its own consequences. So from that the author identifies into two formula problems, namely, related to the defect of will and the consequences faced according to article 1320 of the Covenant. The method used is normative-legal, i.e. seeking such a solution using the literature and regulations available. The result of such an interpretation is that the defect of will contained in a treaty is wrongful to the terms of an agreement in article 1320 of the Covenant and is due to the presence of elements of deceit, coercion, and fraud. In the application of the consequences, then the agreement can be cancelled because it relates to subjective conditions.